Global estimates on the number of persons across the Alzheimer's disease continuum - Gustavsson, Anders; Norton, Nicholas; Fast, Thomas; Frölich, Lutz; Georges, Jean; Holzapfel, Drew; Kirabali, Tunahan; Krolak-Salmon, Pierre; Rossini, Paolo M.; Ferretti, Maria Teresa; Lanman, Lydia; Chadha, Antonella Santuccione; et al. (Alzheimer's and dementia, 2023)
Abstract Introduction Global estimates on numbers of persons in early stages of Alzheimer's disease (AD), including prodromal and preclinical, are lacking, yet are needed to inform policy decisions on preventive measures and planning for future therapies targeting AD pathology. Methods We synthesized the literature on prevalence across the AD continuum and derived a model estimating the number of persons, stratified by 5-year age groups, sex, and disease stage (AD dementia, prodromal AD, and preclinical AD). Results The global number of persons with AD dementia, prodromal AD, and preclinical AD were estimated at 32, 69, and 315 million, respectively. Together they constituted 416 million across the AD continuum, or 22% of all persons aged 50 and above. Discussion Considering predementia stages, the number of persons with AD is much larger than conveyed in available literature. Our estimates are uncertain, especially for predementia stages in low- and middle-income regions where biomarker studies are missing.